E-Wallet, Paylater, and Financial Literacy: Impact on Student Consumption - Pranata, Cahyo Rendi Agung; Wildana, Muhammad Dandy Alif (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The development of e-commerce has triggered fintech companies to create innovative payment methods, as evidenced by the existence of e-wallets and paylater which are currently the most frequently used payment methods in Indonesia. The ease of transactions using fintech e-wallet and paylater and the level of financial literacy may have an impact on people's consumptive behavior, especially in the tech savvy generation. This is interesting to study, which is supported by the different results in previous studies. This study aims to determine the effect of using fintech e-wallet features, paylater, and financial literacy on student consumptive behavior. This research is limited to the use of e-wallet and paylater Shopeepay and Gopay. This research uses a quantitative approach with Structural Equation Model Partial Least Square (SEM-PLS) data analysis techniques. The results of this study indicate that the variable use of e-wallet and the variable use of paylater have a significant effect on student consumptive behavior, while financial literacy has no significant effect on the consumptive behavior of Brawijaya University students.